A plain language summary of the PERSEUS study of daratumumab plus bortezomib, lenalidomide, and dexamethasone for treating newly diagnosed multiple myeloma - Sonneveld, Pieter; Dimopoulos, Meletios A; Boccadoro, Mario; Quach, Hang; Ho, P Joy; Beksac, Meral; Hulin, Cyrille; Antonioli, Elisabetta; Leleu, Xavier; Mangiacavalli, Silvia; Perrot, Aurore; Cavo, Michele; et al. (Future oncology, 2024)
WHAT IS THIS SUMMARY ABOUT?: This summary describes the first analysis of the PERSEUS study, which looked at adults with multiple myeloma that had never been treated before, also called newly diagnosed multiple myeloma. Multiple myeloma is a type of cancer in the blood, specifically in plasma cells within the soft, spongy tissue in the center of most bones, called the bone marrow. Researchers wanted to see if adding daratumumab (D) to a standard treatment of three other medicines called VRd, which stands for bortezomib (V), lenalidomide (R), and dexamethasone (d), could stop the multiple myeloma from getting worse and help participants live longer without multiple myeloma.Half of the participants were assigned to the treatment plan with daratumumab; they received D-VRd during initial treatment phases (induction and consolidation), followed by daratumumab as well as lenalidomide (D-R) in the maintenance phase. The other half of participants received treatment without daratumumab; they received VRd induction and consolidation followed by lenalidomide alone (R) maintenance. In addition, all participants were able to receive an autologous stem cell transplant, a procedure used to further help reduce multiple myeloma. WHAT WERE THE RESULTS?: At the time of this analysis of PERSEUS, about 4 years after participants started the study, participants who received D-VRd treatment followed by D-R maintenance had a better response to treatment (as measured by specific markers of multiple myeloma) and were more likely to be alive and free from their multiple myeloma getting worse in comparison to participants who received VRd followed by R maintenance. Side effects (unwanted or undesirable effects of treatment) in both treatment groups were in line with the known side effects of daratumumab and VRd. WHAT DO THE RESULTS MEAN?: The results of the PERSEUS study showed that including daratumumab in D-VRd induction/consolidation and D-R maintenance was better for treating multiple myeloma than the current standard VRd treatment followed by R maintenance alone in adults with a new diagnosis of multiple myeloma who were also able to receive an autologous stem cell transplant. Of importance, there were no unexpected side effects in either group.Clinical Trial Registration: NCT02874742 (GRIFFIN) (ClinicalTrials.gov).
Keywords: senioři; Treatment Outcome; Multiple Myeloma; výsledek terapie; monoklonální protilátky; Middle Aged; Bortezomib; mužské pohlaví; Antibodies, Monoclonal; Adult; Clinical Trials, Phase II as Topic; Lenalidomide; mnohočetný myelom; ženské pohlaví; bortezomib; Humans; Randomized Controlled Trials as Topic; dexamethason; klinické zkoušky, fáze II jako téma; lidé středního věku; Antineoplastic Combined Chemotherapy Protocols; protokoly protinádorové kombinované chemoterapie; Dexamethasone; dospělí; randomizované kontrolované studie jako téma; Female; Aged; lenalidomid; lidé; Male